A single-source switched-capacitor-based 25-level sextuple boost inverter with a low switch count - Noori, Meysam; Hosseinpour, Majid; Seifi, Ali; Shahparasti, Mahdi (John Wiley & Sons, 2024)
Today, multilevel inverters are widely utilized in various applications. Reducing the number of components in the design of these converters is one of the crucial goals so that they have less volume and cost. This paper presents a single-source structure for a multilevel switched-capacitor inverter with voltage boost capability. The proposed structure can generate 25 sinusoidal-like step voltage levels with a six times amplitude increase compared to the input. This converter uses only one direct current (DC) power source, 14 switches, and four capacitors. The nearest level control switching method has been used to control the converter, create voltage levels, and select the switching modes. A comprehensive comparison has been made with other recently presented structures to demonstrate the efficiency of the proposed structure. The advantages of the proposed structure include using only one DC voltage source, the ability to increase the output voltage six times compared to the input, the use of fewer power electronics components compared to the number of voltage levels, proper efficiency, self-balancing of capacitors, and as a result, the lower cost. The performance accuracy of the proposed converter has been simulated in the MATLAB Simulink environment and then evaluated by a laboratory prototype.
Keywords: multilevel inverter; nearest level switching; power electronics; switched-capacitor; fi=Sähkötekniikka|en=Electrical Engineering|